How does Pycnogenol® influence oxidative damage to DNA and its repair ability in elderly people? - Dvořáková Heroldová, Monika; Paduchová, Zuzana; Muchová, Jana; Ďuračková, Zdeňka; Collins, A. R (Prague Medical Report, 2010)
Our purpose in this randomized, double blind, placebo controlled study was to find out the possible effect of a polyphenolic pine bark extract, Pycnogenol® (Pyc) on the level of 8-oxo-7,8-dihydroguanine (8-oxoG) as representative of oxidative damage to DNA and on the DNA repair ability of elderly people. According to our results, three months of Pyc administration had no effect on the level of oxidative damage to DNA or on repair ability, but we found a relationship between the level of 8-oxoG and repair ability of DNA in this group. To conclude, even if the positive effect of Pyc was not confirmed in the case of elderly people it is important to highlight the necessity of further investigations about the mechanisms of Pyc acting on different age groups.
Keywords: financování organizované; oprava DNA; flavonoidy; guanin; Randomized Controlled Trials as Topic; DNA Damage; Female; oxidační stres; ženské pohlaví; Pinus; Flavonoids; rostlinné extrakty; Oxidative Stress; lidé; dvojitá slepá metoda; DNA Repair; artróza kolenních kloubů; Financing, Organized; Middle Aged; poškození DNA; Double-Blind Method; Male; Comet Assay; Osteoarthritis, Knee; randomizované kontrolované studie jako téma; Plant Extracts; kometový test; Guanine; lidé středního věku; mužské pohlaví; borovice; Humans